Open Access in Humanities and Social Sciences - Ferwerda, Eelco (Septentrio Conference Series, 2014)
See video of the presentation. Ferwerda will talk about the various ways in which the transition to OA is taking place within HSS and STEM disciplines. He will discuss the specific features of many HSS disciplines that need to be taken into account for a successful transition to OA. HSS has different publishing profiles, in some disciplines monographs are still the dominant format. Authors in HSS have different values and a different perspective on Creative Commons licenses. A key driver in the current publication culture is the reputation and reward system. In many countries the way research is funded is also an important issue. Ferwerda will also look at business models for OA publishing and discuss the models that may work for HSS. These and other issues will lead him to the conclusion that a successful transition to OA will require the involvement of all stakeholders in scholarly communication.